Ruddlesden–Popper Hybrid Lead Iodide Perovskite 2D Homologous Semiconductors - Stoumpos, Constantinos C; Cao, Duyen H; Clark, Daniel J; Young, Joshua; Rondinelli, James M; Jang, Joon I; Hupp, Joseph T; Kanatzidis, Mercouri G (Chemistry of materials, 2016)
The hybrid two-dimensional (2D) halide perovskites have recently drawn significant interest because they can serve as excellent photoabsorbers in perovskite solar cells. Here we present the large scale synthesis, crystal structure, and optical characterization of the 2D (CH3(CH2)3NH3)2(CH3NH3) n−1Pb n I3n+1 (n = 1, 2, 3, 4, ∞) perovskites, a family of layered compounds with tunable semiconductor characteristics. These materials consist of well-defined inorganic perovskite layers intercalated with bulky butylammonium cations that act as spacers between these fragments, adopting the crystal structure of the Ruddlesden–Popper type. We find that the perovskite thickness (n) can be synthetically controlled by adjusting the ratio between the spacer cation and the small organic cation, thus allowing the isolation of compounds in pure form and large scale. The orthorhombic crystal structures of (CH3(CH2)3NH3)2(CH3NH3)Pb2I7 (n = 2, Cc2m; a = 8.9470(4), b = 39.347(2) Å, c = 8.8589(6)), (CH3(CH2)3NH3)2(CH3NH3)2Pb3I10 (n = 3, C2cb; a = 8.9275(6), b = 51.959(4) Å, c = 8.8777(6)), and (CH3(CH2)3NH3)2(CH3NH3)3Pb4I13 (n = 4, Cc2m; a = 8.9274(4), b = 64.383(4) Å, c = 8.8816(4)) have been solved by single-crystal X-ray diffraction and are reported here for the first time. The compounds are noncentrosymmetric, as supported by measurements of the nonlinear optical properties of the compounds and density functional theory (DFT) calculations. The band gaps of the series change progressively between 2.43 eV for the n = 1 member to 1.50 eV for the n = ∞ adopting intermediate values of 2.17 eV (n = 2), 2.03 eV (n = 3), and 1.91 eV (n = 4) for those between the two compositional extrema. DFT calculations confirm this experimental trend and predict a direct band gap for all the members of the Ruddlesden–Popper series. The estimated effective masses have values of m h = 0.14 m 0 and m e = 0.08 m 0 for holes and electrons, respectively, and are found to be nearly composition independent. The band gaps of higher n members indicate that these compounds can be used as efficient light absorbers in solar cells, which offer better solution processability and good environmental stability. The compounds exhibit intense room-temperature photoluminescence with emission wavelengths consistent with their energy gaps, 2.35 eV (n = 1), 2.12 eV (n = 2), 2.01 eV (n = 3), and 1.90 eV (n = 4) and point to their potential use in light-emitting diodes. In addition, owing to the low dimensionality and the difference in dielectric properties between the organic spacers and the inorganic perovskite layers, these compounds are naturally occurring multiple quantum well structures, which give rise to stable excitons at room temperature.